2011
DOI: 10.1007/s10512-011-9376-6
|View full text |Cite
|
Sign up to set email alerts
|

246–248Cm Neutron fission cross sections and resonance integrals

Abstract: The fission cross sections of [246][247][248] Cm nuclei for neutron energies 0.1 eV-20 keV have been measured using an SVZ-100 lead moderation time neutron spectrometer at the Institute of Nuclear Research of the Russian Academy of Sciences. The fission resonance integrals have been calculated. The results are compared with the existing data and recommended evaluations.The measurement of the neutron-fission cross sections of Np, Am, and Cm is a priority problem which is important for transmutation of wastes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Assume that the first three moments of the random quantity ξ, which is related with the other random quantities x, y, and z by the relation ξ = ϕ x,y,z , have been measured and their a priori distribution known, where t 0 is the average value, and s i is the variance. Figure 1 shows the fission cross section 〈σ√ ⎯E〉 measured with an SVZ-100 spectrometer in the neutron energy range 0.2eV < E < 400 eV [4]. The expressions for the a posteriori distributions of other random quantities (y, z) have a similar form.…”
mentioning
confidence: 92%
“…Assume that the first three moments of the random quantity ξ, which is related with the other random quantities x, y, and z by the relation ξ = ϕ x,y,z , have been measured and their a priori distribution known, where t 0 is the average value, and s i is the variance. Figure 1 shows the fission cross section 〈σ√ ⎯E〉 measured with an SVZ-100 spectrometer in the neutron energy range 0.2eV < E < 400 eV [4]. The expressions for the a posteriori distributions of other random quantities (y, z) have a similar form.…”
mentioning
confidence: 92%
“…For this reason, in the energy range from thermal to 20 keV the fission cross section of the isotopes 241,242m,243 Am and 243-248 Cm was measured with a spectrometer according to the retardation time of neutrons in lead (jointly with the Institute of Nuclear Research of the Russian Academy of Sciences). The new results showed that the existing evaluations must be re-examined [6].…”
mentioning
confidence: 98%
“…The results were compared with existing data and recommended evaluations.Subbarrier fission cross section of 243 Am in the resonance neutron energy range and the properties of the resonances have not been studied sufficiently to construct reliable data libraries which are necessary to study the transmutation of wastes and to improve models of transitional states in the theory of fission of heavy nuclei.The present work was performed as part of research on the fission of transuranium nuclei using the SVZ-100 lead moderation time neutron spectrometer at the Institute for Nuclear Research of the Russian Academy of Sciences (IYaI RAN) [1][2][3][4][5]. The resonance fission integrals and the area and fission width of the resolved resonances were calculated.…”
mentioning
confidence: 99%
“…The present work was performed as part of research on the fission of transuranium nuclei using the SVZ-100 lead moderation time neutron spectrometer at the Institute for Nuclear Research of the Russian Academy of Sciences (IYaI RAN) [1][2][3][4][5]. Even though their resolution is low, such spectrometers are successfully used to measure nuclide cross sections which are difficult or impossible to study by other methods [6,7].…”
mentioning
confidence: 99%